2021
DOI: 10.1016/j.jneb.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Food Insecurity Nutrition Incentives on Household Fruit and Vegetable Expenditures

Abstract: Objective: Evaluate the impact of the Food Insecurity Nutrition Incentive (FINI) grant program on self-reported fruit and vegetable (FV) expenditures. Design: Pre-post quasi-experimental study design. Setting: Farmers markets and grocery stores in states with FINI projects. Participants: A total of 2,471 Supplemental Nutrition Assistance Program (SNAP) households in 4 intervention groups who lived near a FINI retailer (farmers market or grocery store) and 4 matched comparison groups who did not live near a FIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 10 publications
0
61
0
Order By: Relevance
“…With a change from 7.1% to 16.0% in DUFB use among the study population, the information strategy used appears to be helpful in getting SNAP recipients to participate in the FM incentive program, similar to a previous study [ 16 ]. The change in incentive program use is comparable in magnitude to a multi-state incentive evaluation, which found that 14.6% of their general farmers’ market sample used incentives during the intervention period, up from 11.5% who had previously received incentives before the study [ 24 ]. However, the results presented here indicate a simple information strategy may not be sufficient to motivate usage among SNAP recipients who do not already consume F&V. These individuals may not value the FM incentive program as highly, or experience other barriers such as limited transportation or inconvenient FM operation hours, among others [ 13 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…With a change from 7.1% to 16.0% in DUFB use among the study population, the information strategy used appears to be helpful in getting SNAP recipients to participate in the FM incentive program, similar to a previous study [ 16 ]. The change in incentive program use is comparable in magnitude to a multi-state incentive evaluation, which found that 14.6% of their general farmers’ market sample used incentives during the intervention period, up from 11.5% who had previously received incentives before the study [ 24 ]. However, the results presented here indicate a simple information strategy may not be sufficient to motivate usage among SNAP recipients who do not already consume F&V. These individuals may not value the FM incentive program as highly, or experience other barriers such as limited transportation or inconvenient FM operation hours, among others [ 13 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 93%
“…The change in incentive program use is comparable in magnitude to a multi-state incentive evaluation, which found that 14.6% of their general farmers’ market sample used incentives during the intervention period, up from 11.5% who had previously received incentives before the study [ 24 ]. However, the results presented here indicate a simple information strategy may not be sufficient to motivate usage among SNAP recipients who do not already consume F&V. These individuals may not value the FM incentive program as highly, or experience other barriers such as limited transportation or inconvenient FM operation hours, among others [ 13 , 23 , 24 ]. Among participants who had not previously used the program, 15% reported use after our brief informational intervention, which is much lower than the previously mentioned clinical intervention, which resulted in 61% of participants using the program [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Healthy food incentive programs, such as the USDA Healthy Incentives Program and the Gus Schumacher Nutrition Incentive Program (GusNIP), have been shown to increase fruit and vegetable expenditure and intake [11][12][13], reduce food insecurity [14], and improve healthy eating behaviors [15]. Although effective, these programs are underutilized, with only a small fraction of SNAP participants having access to them [15].…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies, including local farming collectives, neighborhood gardens, increasing access through free delivery and drop-off points, and healthy incentive programs, are necessary to provide food to households at the greatest risk [10]. Healthy food incentive programs, in particular, have been shown to improve food security, increase fruit and vegetable expenditures and intake, and improve healthy eating behaviors [11][12][13][14][15][16][17]. Partnerships between non-profits and grocery retail stores have been shown to be effective at creating incentive programs [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%